NORMAL STANDAR KLIMATOLOGI UNTUK PEMETAAN POTENSI ENERGI ANGIN DAN SIMULASINYA DI WILAYAH KALIMANTAN BARAT - Firsta Zukhrufiana Setiawati; Ananggirieza Nugraha2 (Jurnal Meteorologi Klimatologi dan Geofisika, 2020)
Today, there are more and varied researches on renewable energy, including on utilization of wind energy. Wind energy has been used to generate 147 MW of electricity in Sidrap and Jeneponto (South Sulawesi). The present study is prepared to determine the amount of wind energy potential and its capability in the power produced in West Kalimantan. The study was performed using statistic calculation and analysis by using data of wind speed at an altitude of 10 meters above ground level from manual observation and PSD reanalysis, NOAA. The research result shows that wind energy potential is relatively low in June and December, as shown in the map of wind energy potential based on climatological standard normal. Following shear pattern on streamline, central West Kalimantan has the lowest wind energy potential (< 25 W/m2). The highest wind energy potential is in Ketapang Regency (Tumbang Titi Sub-district) which is > 52 W/m2). HOMER simulation for Tumbang Titi shows wind energy potential can be used to generate into 9,457 kWh/year and requires $4,071.15, with most of the expenses for wind turbine which amounts to $3,632.61.